Evaluation the effects of Omega-3 and vitamin C alone or in combination on Methotrexate-Induced hepatotoxicity (in mice) - Doha Mohammed; Ali Mohammed Al-Gareeb (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the effect of pretreatment with omega-3 alone or in combination with vitamin C on hepatotoxicity raised by methotrexate. Method: The experimental study was conducted at the animal house of the Iraqi Centre of Cancer Research and Medical Genetics and the Department of Pharmacology, College of Medicine, Al-Mustansiriyah University, Baghdad, Iraq, from November 2020 to July 2021, and comprised Swiss albino mice who were divided into 5 groups. Group A was treated with normal saline, group B was injected with methotrexate 20mg/kg intraperitoneally, group C was pretreated with omega 3 100mg/kg, group D was pretreated with vitamin C 100mg/kg, and group E was pretreated with concomitant vitamin C and omega 3 100mg/kg. The intervention lasted 9 days in each group, and were injected with methotrexate on day 10. The mice were sacrificed under chloroform anaesthesia after 48 hours. Blood sample was taken for biochemical examination. One part of liver was preserved in formalin 10% for histopathological study. Results: Of the 35 mice, there were 7(20%) in each of the 5 groups. There was a significant increase in malondialdehyde and lactate dehydrogenase levels and a decrease in the superoxide dismutase and glutathione (p<0.05). Conclusion: Pretreatment with omega-3 and vitamin C ameliorated the hepatotoxicity induced by methotrexate due to strong antioxidant, anti-inflammatory and anti-apoptotic effects. Key Words: Antioxidants, Methotrexate, Chloroform, Saline, Glutathione, Liver, Malondialdehyde, Superoxide, Lactate Dehydrogenases, Ascorbic Acid, Formaldehyde